2016
DOI: 10.1371/journal.pone.0157657
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Increasing Influenza Vaccination Coverage in Adults with Type 2 Diabetes in Turkey

Abstract: ObjectiveIn Turkey, the prevalence of diabetes is high but the influenza vaccination coverage rate (VCR) is low (9.1% in 2014), despite vaccination being recommended and reimbursed. This study evaluated the cost-effectiveness of increasing the influenza VCR of adults with type 2 diabetes in Turkey to 20%.MethodsA decision-analytic model was adapted to Turkey using data derived from published sources. Direct medical costs and indirect costs due to productivity loss were included in the societal perspective. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…This study confirmed previous reports that the rates of pneumococcal and influenza vaccination are low in Turkey. 24,26,27 The findings of this study reflect real-life data and it allowed us to identify an area where efforts should be directed. As the main determinant for receiving one of the vaccines is the receipt of the other, it appears that awareness drives vaccination.…”
Section: Discussionmentioning
confidence: 56%
“…This study confirmed previous reports that the rates of pneumococcal and influenza vaccination are low in Turkey. 24,26,27 The findings of this study reflect real-life data and it allowed us to identify an area where efforts should be directed. As the main determinant for receiving one of the vaccines is the receipt of the other, it appears that awareness drives vaccination.…”
Section: Discussionmentioning
confidence: 56%
“…There have been several guidelines recommending influenza vaccination for patients with T2DM [14,15,16,17,18], and many countries have incorporated influenza vaccines into their national immunisation plans [26]. An assessment of the cost-effectiveness of influenza vaccination for patients with T2DM in Turkey demonstrated that an increase in the vaccination rate from 9.1% to 20% was cost-effective according to WHO guidelines [27]. In accordance with the recognition of its benefits for patients with T2DM, the city of Ningbo began in 2016 to promote the influenza vaccine for this population.…”
Section: Discussionmentioning
confidence: 99%
“…Adult and at-risk pneumococcal and influenza vaccination data were obtained from [ 5 ] and: Andorra [ 108 ]; Argentina [ 109 , 110 ]; Belgium [ 111 ]; Brazil [ 112 ]; Central and Eastern Europe [ 113 ]; Denmark [ 114 , 115 ]; European nations [ 85 , 116 , 117 , 118 , 119 ]; Europe and Gulf nations [ 120 ]; Germany [ 121 ]; Gulf nations [ 122 , 123 ]; Hong Kong [ 124 ]; Hungary [ 125 ]; Iceland [ 126 ]; Ireland [ 127 ]; Israel [ 128 ]; Latin America [ 129 ]; Mexico [ 130 , 131 ]; New Zealand [ 132 ]; Poland [ 133 ]; Qatar [ 134 ]; San Marino [ 135 ]; Singapore [ 136 ]; Slovenia [ 137 ]; South Africa [ 138 ]; Sweden [ 139 ]; Switzerland [ 140 , 141 , 142 ]; Taiwan [ 143 , 144 , 145 ]; Turkey [ 146 , 147 , 148 ]; and U.K. [ 149 ]. All of these data are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%